Negative moods correlate with craving in female methamphetamine users enrolled in compulsory detoxification - Shen, Wenwen (BioMed Central, 2012)
BACKGROUND: Methamphetamine (METH) use, especially in females, has become a growing public health concern in China. In this study, we aimed to characterize the factors that contributed to drug craving in female METH users under isolated compulsory detoxification. We characterized factors contributing to craving such as duration of detoxification, history of drug use and self-reported mood state. METHODS: Subjects (N=113) undergoing a 1- to 3-year METH detoxification program were recruited from the Zhejiang Compulsory Detoxification Center for Women. The Questionnaire of METH-use Urge (QMU) was used to evaluate the level of craving for METH. The Abbreviate Profile of Mood States (A-POMS) was applied as an assessment for the negative mood disturbances. RESULTS: The participants were at a mean age of 25.2, primarily lowly educated and unemployed, and single. Smoking was the only route of METH administration at an average dose of 0.5 g/day, and 4 times/week. The reported craving level was positively correlated with the negative mood disturbances and the weekly dose of METH, but independent of the duration of detoxification. Furthermore, all five aspects of negative mood disturbances, including fatigue, bewilderment, anxiety, depression and hostility, were shown to positively correlate to the self-reported craving level after controlling for weekly dose of METH. CONCLUSIONS: The data demonstrate a robust correlation between mood distress and craving for METH. Our results call for close evaluation of mood distress in treatment of METH users in China.